Tumor-Derived Lactate Creates a Favorable Niche for Tumor via Supplying Energy Source for Tumor and Modulating the Tumor Microenvironment - Jin, Mengyao; Cao, Wei; Chen, Bo; Xiong, Maoming; Cao, Guodong (Frontiers in Cell and Developmental Biology, 2022)
Tumor evolution is influenced by events involving tumor cells and the environment in which they live, known as the tumor microenvironment (TME). TME is a functional and structural niche composed of tumor cells, endothelial cells (ECs), cancer-associated fibroblasts (CAFs), mesenchymal stromal cells (MSCs), and a subset of immune cells (macrophages, dendritic cells, natural killer cells, T cells, B cells). Otto Warburg revealed the Warburg effect in 1923, a characteristic metabolic mechanism of tumor cells that performs high glucose uptake and excessive lactate formation even in abundant oxygen. Tumor tissues excrete a large amount of lactate into the extracellular microenvironment in response to TME’s hypoxic or semi-hypoxic state. High lactate concentrations in tumor biopsies have been linked to metastasis and poor clinical outcome. This indicates that the metabolite may play a role in carcinogenesis and lead to immune escape in TME. Lactate is now recognized as an essential carbon source for cellular metabolism and as a signaling molecule in TME, forming an active niche that influences tumor progression. This review summarized the advanced literature demonstrating the functional role of lactate in TME remodeling, elucidating how lactate shapes the behavior and the phenotype of both tumor cells and tumor-associated cells. We also concluded the intriguing interactions of multiple immune cells in TME. Additionally, we demonstrated how lactate functioned as a novel function factor by being used in a new histone modification, histone lysine lactylation, and to regulate gene expression in TME. Ultimately, because lactate created a favorable niche for tumor progression, we summarized potential anti-tumor strategies targeting lactate metabolism and signaling to investigate better cancer treatment.